Rousseau meets Azuma - Martin Roth; Fabian Schäfer (Minikomi, 2021)
An imagined conversation between Azuma Hiroki and an old man (maybe Jean-Jacques Rousseau) regarding their ideas about "Social Contract" and "General Will 2.0".